The influence of CEO’s financial literacy on SMEs technological innovation: the mediating effects of MCS and risk‑taking. - Duréndez, Antonio; Diéguez-Soto, Julio; Madrid-Guijarro, Antonia (Springer Nature, 2023)
Previous literature showed mixed results about the impact of CEOs’ financial literacy (CFL) on small and medium-sized enterprises’ (SMEs) innovation. This relationship can be motivated by relevant variables, which are missing in the previous literature and make a difference as mediators. In this sense, based on the theoretical framework related to upper echelon theory and resource-based view, this study focuses on the mediating effect of risk-taking attitude and management control systems (MCS) variables. Empirical data from 310 SMEs gathered using a qualitative research questionnaire are analyzed using structural equation modeling methodology. Specifically, estimations are carried out considering the partial least square method. Findings show that MCS and managers’ risk attitudes fully mediate the relationship between financial literacy (FL) and innovation. Between these two mediating variables, the implementation of MCS stands out because it also enables the mediating effect of CEOs’ risk-taking in the CFL–technological innovation relationship. As the results do not support the significant direct relationship between FL and risk attitude, they confirm an indirect effect through MCS. Furthermore, based on the study findings, SMEs’ directors and owners, business associations, and public authorities can improve SMEs’ technological innovation by implementing training programs and policies to foster CFL. They can also acknowledge the interdependency between organizational factors and individual characteristics to enhance SMEs’ technological innovation.
Keywords: Pequeñas y medianas empresas; Educación financiera; Financial literacy; Technological innovation; Management control systems; Risk-taking